2015
DOI: 10.1080/14708477.2014.993648
|View full text |Cite
|
Sign up to set email alerts
|

Identity and language: Korean speaking Korean, Korean-American speaking Korean and English?

Abstract: The identity formation of a diaspora community is complex. The present study examines native language maintenance and ethnic identity of first-, 1.5-, and secondgeneration Korean-Americans in the United States, through the lenses of various identity construction and sociolinguistic theories. Identity and language are closely linked, and this relationship is bound by social contexts. Both identity and language are viewed as dynamic and mutable. The study also identifies social factors that affect linguistic beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…This study investigated how parental cultural maintenance behaviour and language usage at home relate to national identity, ethnic identity, and well-being among adolescents in the multiethnic and multilingual context of Indonesia. In line with the previous studies (Rotheram and Phinney 1987;Smith et al 1999;Phinney, Romero et al 2001;Downie et al 2007;Han 2010;Dimitrova et al 2013Dimitrova et al , 2014Choi 2015), our results show that parental culture maintenance behaviour is positively associated with both national and ethnic identity, which in turn is positively associated with well-being; this study is the first providing this evidence for Indonesian adolescents. Previous studies have shown that identity and language are closely linked (Le Page 1972;Phinney, Romero et al 2001;Choi 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study investigated how parental cultural maintenance behaviour and language usage at home relate to national identity, ethnic identity, and well-being among adolescents in the multiethnic and multilingual context of Indonesia. In line with the previous studies (Rotheram and Phinney 1987;Smith et al 1999;Phinney, Romero et al 2001;Downie et al 2007;Han 2010;Dimitrova et al 2013Dimitrova et al , 2014Choi 2015), our results show that parental culture maintenance behaviour is positively associated with both national and ethnic identity, which in turn is positively associated with well-being; this study is the first providing this evidence for Indonesian adolescents. Previous studies have shown that identity and language are closely linked (Le Page 1972;Phinney, Romero et al 2001;Choi 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Identity, language, and well-being Identity and language tend to be closely linked (Le Page 1972;Phinney, Romero et al 2001;Choi 2015). In multicultural nations, language not only demarcates membership of an ethnic group but also signifies bonds across ethnic lines and enhances a sense of ethnic and national identity, because language enables a person to be ethnically rooted and yet to reach out communicatively at a national level (Das Gupta 1968).…”
mentioning
confidence: 99%
“…Language is the most significant element of Korean ethnicity. Koreans can speak, write and read in Korean, and it has strengthened their ties to the ethnic community in the USA and Korean Peninsula (Choi, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Discussions of intercultural communication and intercultural competence have for a long time tended to have a largely Euro-or Asia-centric orientation in relation to the participants under discussion, often in relation to the learning of English. Comparatively less has been written about these matters from the perspective of learning other languages (but see Choi, 2015;Fay & Davcheva, 2014;McNamara, 2013 for exceptions), or from the position of learners of languages other than English who are themselves located within an Anglophone context (but cf. Quist, 2013).…”
Section: The Ecological Context Of Studying Mandarin In British Univementioning
confidence: 99%